کرنسی کےبارے میں مولانا احمد رضا خانؒ کی کتاب کفل الفقیہ الفاھم کا خصوصی مطالعہ: Kifal al-Faqīh al-Fāhim by Imam Ahmed Raza Khan: A Special Study - Dr. Ali Akbar Alazhari; Dr. Manzoor Ahmad al-Azhare (MEI, 2023)
This paper aims to highlight the scholarly discourse regarding money, cash and currency notes (nuqud) as well as Shariah injunctions in this regard tackling twelve queries about what is currency notes and its merits and demerit as a medium of exchange or is there any intrinsic value of paper money or not considering the valuable opinions of scholars about salient features of paper money. This Religio-Economic discourse also depicts the insight of jurists approach when there was no prominent working in the world within the traditional circle about the subject study. This article analytically judges the various outlooks and stances of Islamic scholars with brief historical sketch about currency along with number of contemporary scholars and their standpoints from Egypt and Pakistan etc. Is there any relation of cash with usury (Riba) having storage value and some other relevant questions about alms due (Zakat), paper money and marriage dowry have also been addressed. Hence, the note is not just a certificate but a source of payment, exchange of good and guarantee of commodity